2022
DOI: 10.3390/ani12192717
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Inflammatory and Regenerative Effects of Autologous Conditioned Serum from Dogs with Osteoarthritis

Abstract: Osteoarthritis (OA) is mostly incurable and non-regenerative with long-term complications. Autologous conditioned serum (ACS), which is enriched in Interleukin 1 receptor antagonists (IL-1RA) and growth factors, could be an alternative treatment to accelerate the positive therapeutic effects. ACS is proposed to alleviate inflammation by blocking IL-1 receptors. However, to date, there is no report focusing on the cell-mediated anti-inflammation and regenerative effect caused by ACS, especially the ACS from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…62 ACS obtained from dogs with naturally occurring osteoarthritis was evaluated in vitro. 9 The ca-nine ACS in this study included significantly increased concentrations of IL-1RA, vascular endothelial growth factor, and TGF-β. In chondrocyte cell cultures, antiinflammatory effects were identified, as were proliferation of fibroblasts and osteocytes, and extracellular matrix gene expression was elevated.…”
Section: Autologous Conditioned Serummentioning
confidence: 96%
See 2 more Smart Citations
“…62 ACS obtained from dogs with naturally occurring osteoarthritis was evaluated in vitro. 9 The ca-nine ACS in this study included significantly increased concentrations of IL-1RA, vascular endothelial growth factor, and TGF-β. In chondrocyte cell cultures, antiinflammatory effects were identified, as were proliferation of fibroblasts and osteocytes, and extracellular matrix gene expression was elevated.…”
Section: Autologous Conditioned Serummentioning
confidence: 96%
“…ACStreated tendons had reduced lameness and swelling and increased collagen type I expression compared to controls. 8 An in vitro study 9 reported ACS sourced from dogs with osteoarthritis had anti-inflammatory and regenerative activity. The authors concluded that the hemoderivatives from dogs with arthritis contained the bioactive factors that would be appropriately used for osteoarthritis management.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of OA treatment, they represent an advantage when compared with traditional intra-articular treatments (HyA + SAIDs), which are only palliative for pain and inflammation control [161] as they improve clinical signs and appear to be chondrogenic and promote chondrocyte homeostasis [161][162][163]. In cases of tendonitis/desmitis, they also present therapeutic effects, enhancing healing, and leading to the formation of functional tissue without scar formation [164,165].…”
Section: Hemoderivativesmentioning
confidence: 99%
“…5,6 The limited regeneration potential of articular cartilage and the progression of osteoarthritis necessitate new methods to improve joint healing and functional outcome. 9,10 One of these concepts is the use of autologous conditioned plasma (ACP) or platelet-rich plasma (PRP). The theoretical efficacy of ACP is based on the physiological role of thrombocytes in wound healing.…”
Section: Introductionmentioning
confidence: 99%